Community-based turmeric tea intervention for hyperuricemic elderly in Manado, Indonesia - Ellen Pesak; Ni Luh Jayanthi Desyani; Tinneke A. Tololiu; Jane Annita Kolompoy; Herlina P. Memah; Bongakaraeng Bongakaraeng; Rommy David Watuseke; Yanni Karundeng; Lorrien Grace Runtu; Debora Yuriska Rau (Intelektual Pustaka Media Utama, 2026)
Hyperuricemia, with a global prevalence of approximately 14.0% in the general population and rising to 24.0% among the elderly, represents the second most prevalent metabolic disease after diabetes and constitutes a significant public health burden. This study aimed to determine the effectiveness of turmeric tea in reducing blood uric acid levels in hyperuricemic elderly. A quasi-experimental design with a pretest-posttest control group approach was employed, involving 140 respondents equally divided into an intervention group (n = 70) receiving 1000 mg/day of turmeric tea and a control group (n = 70) receiving standard health education. Blood uric acid levels were measured using a portable uric acid meter. Data were analyzed using the Paired Sample t-test, the Independent Sample t-test, and multiple linear regression. The intervention group demonstrated a significant reduction in mean uric acid levels from 8.46 ± 1.32 mg/dL to 6.78 ± 1.18 mg/dL (mean difference = 1.68 mg/dL; p = 0.000), while the control group showed no significant change (8.39 ± 1.28 to 8.21 ± 1.25 mg/dL; p = 0.137). The effect size was large (Cohen's d = 1.23). Multiple regression confirmed turmeric tea as the strongest predictor of uric acid reduction (B = 1.472; p = 0.000). Turmeric tea effectively reduces blood uric acid levels in hyperuricemic elderly and holds potential for integration into community-based elderly health programs as an accessible and affordable complementary therapy for hyperuricemia management.